Revisión del efecto Kerr magneto óptico (2009)
ABSTRACT: In this work we review the deduction of Fresnell coefficient for the reflexion of polarized light over a magnetized medium. We obtained the expressions for the Kerr angle in both polar and equatorial case. It is shown that the effect polar magneto-optic effect is two order stronger than the equatorial. This treatment is only valid for magnetic field weaker than 10 T.